2003
DOI: 10.1007/s00330-003-1833-8
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal nerve injury in three patients with knee trauma: MR imaging and correlation with anatomic findings in volunteers and anatomic specimens

Abstract: The aim of this article is to report on three patients with injuries of the peroneal nerve along the posterolateral aspect of the knee. Injuries in this area are less common than the injuries occurring at the level of the fibular head. In this article we report on three patients with posterolateral knee trauma who had peroneal nerve dysfunction. To better understand the precise location of the nerve on MR images, we performed MR imaging in five volunteers, and studied the position of the nerve on anatomic diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
0
16
0
2
Order By: Relevance
“…4,5,10,15 The mechanism has been thought to be a stretch lesion to the posterolateral aspect of the knee. 24 Because of the broad zone of injury seen clinically, patients often fare poorly and do not recover either spontaneously or even when treated with long interpositional grafts. Salvage procedures such as posterior tibialis tendon transfer may be necessary to eliminate the need for an ankle-foot orthosis.…”
mentioning
confidence: 99%
“…4,5,10,15 The mechanism has been thought to be a stretch lesion to the posterolateral aspect of the knee. 24 Because of the broad zone of injury seen clinically, patients often fare poorly and do not recover either spontaneously or even when treated with long interpositional grafts. Salvage procedures such as posterior tibialis tendon transfer may be necessary to eliminate the need for an ankle-foot orthosis.…”
mentioning
confidence: 99%
“…Different methods have been described for imaging-anatomic correlation [1,3]. A few studies made correlations between anatomic specimens and ultrasound findings [4,5]. We describe a new method for ultrasound-anatomic correlation.…”
Section: Discussionmentioning
confidence: 98%
“…In CT and MR imaging, correlations with anatomic dissection or anatomic slices have been widely performed, especially in certain subspecialty areas such as musculoskeletal imaging [1,2,3,4,5]. The use of such correlation methods is less well developed in the field of ultrasound.…”
Section: Introductionmentioning
confidence: 98%
“…In the presence of a nerve pathology, MRI can provide information about the distance between the nerve ends when there is complete disruption, presence of constrictive perineural scar tissue, posttraumatic neuroma in chronic injuries surrounding edema, encasing hematoma in the epineurium, mild contusion, and partial disruption of the fibers. 25,44 Peltola et al 26 found a high correlation between patients who had no clinical signs or symptoms of peroneal nerve injury and normal peroneal nerve findings on MRI.…”
Section: Mrimentioning
confidence: 99%
“…26,44 The CPN is typically adjacent to the posterior margin of the biceps tendon and deep to the crural fascia in the posterolateral aspect of the knee. In the presence of a nerve pathology, MRI can provide information about the distance between the nerve ends when there is complete disruption, presence of constrictive perineural scar tissue, posttraumatic neuroma in chronic injuries surrounding edema, encasing hematoma in the epineurium, mild contusion, and partial disruption of the fibers.…”
Section: Mrimentioning
confidence: 99%